Surgical resection of endolymphatic sac tumors in von Hippel‐Lindau disease: Findings, results, and indications12. (15th October 2012) - Kim, H. Jeffrey; Hagan, Marygrace; Butman, John A.; Baggenstos, Martin; Brewer, Carmen; Zalewski, Christopher; Linehan, W. Marston; Lonser, Russell R.
Abstract Objectives/Hypothesis: To define the surgical treatment and outcomes of von Hippel‐Lindau (VHL) disease‐associated endolymphatic sac tumors (ELSTs), we analyzed consecutive VHL patients who underwent ELST resection. Study Design: Retrospective investigation of consecutive VHL patients who underwent resection of ELSTs at a clinical research center between 1999 and 2010. Methods: Analysis of serial clinical examinations, audiograms, imaging studies, and operative findings were analyzed. Results: Thirty‐one consecutive patients with ELSTs (15 males, 16 females) underwent resection of 33 tumors (mean follow‐up, 49.9 ± 48.0 months; range, 1.0–116 months). One patient had bilateral ELST resections and one patient underwent reoperation for recurrence. Mean age at surgery was 38.2 ± 10.2 years (range, 12–67 years). Whereas 29 ears (88%) had direct radiographic evidence of an ELST, four ears (12%) did not. Mean tumor size was 1.3 ± 1.1 cm (range, 0.2–5.2 cm). Whereas two patients (two ears, 6%) were asymptomatic, 29 patients (31 ears, 94% of ears) had associated audiovestibular symptoms, including sensorineural hearing loss (28 ears, 84%), tinnitus (24 ears, 73%), and vertigo (21 patients, 68%). Postoperatively, hearing was stabilized (27) or improved (three) in 97% of 31 ears. Complete tumor resection was achieved in 30 ears (91% of 33 ears). Complications included cerebrospinal fluid leak in two ears (6%) and transient lower cranial nerve palsy in one ear (3%). Conclusions: Surgical resection of ELSTs can be performed with hearing preservation and a reduction in audiovestibular dysfunction. Early surgical resection can prevent or decrease disabling audiovestibular symptoms, enhance the opportunity for complete resection, and preserve hearing. Laryngoscope, 2012